Transcytosis, Antitumor Activity and Toxicity of Staphylococcal Enterotoxin C2 as an Oral Administration Protein Drug - Zhao, Wenbin (Toxins (Basel), 2016)
Staphylococcal enterotoxin C2 (SEC2) is a classical superantigen (SAg), which can tremendously activate T lymphocytes at very low dosage, thus exerting its powerful antitumor activity. As an intravenous protein drug and a bacterial toxin, SEC2 has some limitations including poor patient compliance and toxic side effects. In this research, we devoted our attention to studying the antitumor activity and toxicity of SEC2 as a potential oral administration protein drug. We proved that His-tagged SEC2 (SEC2-His) could undergo facilitated transcytosis on human colon adenocarcinoma (Caco-2) cells and SEC2-His was detected in the blood of rats after oral administration. Furthermore, oral SEC2-His caused massive cytokine release and immune cell enrichment around tumor tissue, leading to inhibition of tumor growth in vivo. Meanwhile, although SEC2-His was dosed up to 32 mg/kg in mice, no significant toxicity was observed. These data showed that SEC2 can cross the intestinal epithelium in an immunologically integral form, maintaining antitumor activity but with reduced systemic toxicity. Therefore, these results may have implications for developing SEC2 as an oral administration protein drug.